(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Traditional management of Visha Chikitsa involves many practices that are yet to be explored. Keraleeya Visha Chikitsa Granthas possess abundant knowledge of practically used formulations in treatment of Visha as well as its complications. Vishaja Vrana can be considered as Aganthuja Vrana which has to be managed at time to prevent its complications. Vrana hara Yogas with specific indication will be working more effectively in this condition. Visha Jyotsnika, a book written in Malayalam which explains about the treatment practices followed by Visha Vaidyas from time to time in a practicable approach. Mandali Visha Chikitsa is explained in sixth chapter in detail along with various Vranahara yogas. This article highlights about the probable mode of action of Panktiprasoonadi ghritham in Vishaja Vrana. Dasa Pushpa, the divya aushadhi for Visha being the main ingredient in this formulation along with the combination of other Vrana Ropana drugs like Kupilu, Haridra, Yastimadhu, Sariva etc as a Ghrita preparation will be an excellent option for managing Vishaja Vrana from its initial condition.